pengaruh bahasa daerah pada proses diskusi mahasiswa 1E pgmi uin sultan thaha Saifuddin jambi - sefty Sefty ramadhani (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2026)
Abstract This study aims to analyze the influence of regional language use on the discussion process of students in Class 1E of the Islamic Elementary Teacher Education (PGMI) Study Program at UIN Sultan Thaha Saifuddin Jambi. The research employed a qualitative approach with a field research design to obtain an in-depth understanding of students’ experiences, perceptions, and empirical conditions during classroom discussions. Data were collected through in-depth interviews, direct observation, and documentation involving students selected through purposive sampling, supported by additional informants from course lecturers. Data analysis was conducted qualitatively through the stages of data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that the use of regional languages has a significant influence on the student discussion process. Regional languages tend to increase students’ confidence, activeness, and spontaneity in expressing opinions and participating in discussions. However, the dominant use of regional languages may also create communication barriers for students who do not share the same linguistic background, thereby affecting mutual understanding and the equal distribution of participation. These findings suggest that regional language use in academic discussions has a dual impact, functioning both as a facilitator of student engagement and as a